Citizenship Behavior Questionnaire-30–General Version: Evidence of measurement invariance among university students from Poland and Taiwan - Chifa Hung; Agata Chudzicka-Czupała; Anna M. Zalewska; Barbara Ostafińska-Molik; Magdalena Ludwik; Bartosz Grabski; Chung-Ying Lin; Cheng-Fang Yen (Acta Psychologica)
Background: The Citizenship Behavior Questionnaire-30–General Version (CBQ-30-GV) evaluates multidimensional citizenship behaviors (CBs), yet its measurement invariance across country and gender groups remains unexamined. This study evaluated the measurement invariance of the CBQ-30-GV across country (Poland vs. Taiwan) and gender (female vs. male) groups. Methods: A cross-sectional design with convenience sampling was employed. A total of 1062 Polish and 1000 Taiwanese university students completed online surveys. Three nested multigroup confirmatory factor analysis models—a configural model, a metric invariance model, and a scalar invariance model—were tested in a bifactor framework incorporating a general CB factor and several specific CB factors to assess the measurement invariance of the CBQ-30-GV across country and gender groups. Results: The configural model exhibited good fit (comparative fit index = 0.924), supporting the bifactor structure. However, no full invariance across country groups was established. Partial invariance was achieved by relaxing certain item loadings, indicating that Polish and Taiwanese students may interpret some items differently. By contrast, full invariance was supported across gender groups. Conclusion: The CBQ-30-GV is suitable for assessing multidimensional CBs among university students. However, cross-country comparisons between Polish and Taiwanese students should be conducted with caution as a result of partial invariance. The measurement invariance of the CBQ-30-GV across gender groups is supported, supporting its use for comparing CBs between female and male students in the future.